2022
DOI: 10.1177/10776990221130992
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Audience Verification Intention: The Impact of Partisanship, Source, Importance, and Information Familiarity on Willingness to Verify Headlines

Abstract: This study employed a 2 × 3 × 2 experiment in the United States to understand how headlines trigger willingness to verify information, manipulating partisan leaning, source credibility, and factuality. Based on evolutionary psychology, we also explored how perceived importance and information familiarity influence willingness to verify information for accuracy or confirmation of preexisting beliefs. Findings show no differences between accuracy (truth-seeking) and confirmation motivations, both driven mainly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Next, impacts on attitudes and policy preferences were more likely for individuals who saw an ideologically congruent argument from a cable news source they trust. These results are in line with recent research suggesting that the confirmation of preexisting attitudes serves as a stronger incentive during news consumption than does a desire to be accurate (Mourão et al, 2023). Both of our experimental studies showed that getting information from a trusted cable news source contributes to the reinforcement of congruent attitudes about high-salience political issues.…”
Section: Discussionsupporting
confidence: 92%
“…Next, impacts on attitudes and policy preferences were more likely for individuals who saw an ideologically congruent argument from a cable news source they trust. These results are in line with recent research suggesting that the confirmation of preexisting attitudes serves as a stronger incentive during news consumption than does a desire to be accurate (Mourão et al, 2023). Both of our experimental studies showed that getting information from a trusted cable news source contributes to the reinforcement of congruent attitudes about high-salience political issues.…”
Section: Discussionsupporting
confidence: 92%
“…This suggested that people verify less so for the purposes of reducing uncertainty, but rather to reaffirm their existing partisan beliefs. Mourão et al (2022) extended these findings by exploring what factors drove partisans to verify information and found that conservatives were more likely to verify based on credible sources congruent with their political identity while liberals relied on their degree of familiarity with the news headline rather than its ideological alignment. Both U.S.-based studies mentioned earlier pointed to "directional motivated reasoning" as a fundamental cognitive driver in which individuals judge the veracity of political content and subsequent intentions to engage with it (Flynn et al, 2017).…”
Section: Information Credibility and Audience Verification Behaviorsmentioning
confidence: 86%
“…This was rarely the case, which suggested selective avoidance (on a group level) is the likely explanation for the distinctive headline selections in crossover conditions with a more believable headline attributed to a distrusted source. Future research should take into account other potential selective exposure and avoidance mechanisms, such as attentiveness, entertainment-value, topic-curiosity, prior knowledge, or issue salience, as well as accuracy, impression, confirmation-seeking, and truth-seeking motivations (see Mourão et al, 2023;Winter et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As aggregate groups with opposing positions on news source trust for CNN and Fox News, as well as positions on global warming (see Tully et al, 2020), it was expected that they behaved contrarily in selecting headlines. In fact, as congruent headlines have usually been considered more truthful than incongruent headlines (Mourão et al, 2023), in many instances, it would be anticipated that Biden voters would mainly prefer one headline and Trump voters prefer the other when the headlines depict opposite positions on global warming. However, that difference may only disappear because of a substantial group of people's need to avoid selecting headlines from a distrusted source even when such headlines are considered congruent with the individuals' beliefs.…”
Section: Headline Selectionmentioning
confidence: 99%